Iran Diabetes Research Roadmap (IDRR) Study; Trends of Pub-lications in Management of Diabetes in Iran: A Review Article - Gita SHAFIEE; Fatemeh BANDARIAN; Maryam GHODSI; Ensieh NASLI-ESFAHANI; Bagher LARIJANI (Tehran University of Medical Sciences, 2017)
Background: This study conducted to assess publications of diabetes treatments to understand research gaps and priorities to guide a management map for future strategy of diabetes research in Iran. Methods: All studies published from the beginning until 2015 in national and international journals by Iranian authors conducted in the field of diabetes. This comprehensive search strategy without any limitation obtained 8668 publications in international journals and 16921 documents in national journals (25589 documents). Finally, 1019 diabetes management articles were included in this study. Each article categorized based on the study design, subject area, the World Health Organization (WHO) classification and Australian Standard Research Classifications. Results: There was an increasing trend in a number of publications. Top subject areas were "traditional treatment" with global publication share of 25.8% and "Control of diabetes" ranked the second (24.9%). According to WHO classification, the highest number of productions was in "Basic Research" area (39%) and Australian Standard Research Classification showed 59% of the articles were in "Clinical Medicine and Science" area. Study design of 39.9% articles was basic studies, 23.1% were randomized clinical trial and 21.9% were cross-sectional. Conclusion: This study showed a relatively ascending trend of scientific publications in the field of diabetes managements in Iran. We can identify the research gaps and research priorities for diabetes management research for future studies. In Future, management map with other diabetes area research maps will be compiled into a single "Roadmap for Diabetes Research in Iran".